Una Destinatio, Viae Diversae – One Destination, Many Paths: An Invitation to Design Curriculum - Aviva B Dorfman (Networks: An Online Journal for Teacher Research, 2018)
One goal of early childhood teacher educators is to teach in ways that model teaching young children. What better way to study curriculum than to design it? This article describes a graduate early childhood curriculum course in which the students participate in the process of designing the syllabus. They receive a syllabus empty of topics, schedule, and readings. Together, we design the course according to their interests and needs. By semester’s end there is a full reading list and schedule. The invitation to co-design curriculum provides opportunities for investigation, representation and reflection as does constructivist teaching for children, and demonstrates concretely that curricular goals can be addressed in multiple and varied ways.
Keywords: Teacher education; teaching; early childhood; curriculum